Educação e instrução na Filosofia Política de Eric Weil - Uchôa, Marcela da Silva (2013)
This work will focus on explaining the concepts of Instruction and Education of Eric Weil, as well as the relation between them, which is a fundamental tool for effecting a reasonable action, which shows the extremely ethical sense of philosophy in Weil’s thought. The thought of the philosopher reflects the issue of education under the aspect of morality. The formal Kantian morality can be used as a basis for Weil reflection on the reasonable educational action. According to Weil, the historical role of the educator is to teach the individual to discern the reason in the world, since the goal of education is to offer the violent individual a way of virtuous acting with other community members. Hence derive the differences between education and instruction. The overvaluation of the instruction, the demand for skills and training of skilled labor for the capitalist system hide what should be the true meaning of education which is to educate men to undergo spontaneously to the universal law (natural), an education in opposite of being a slave of passions and to be held by them.